Social Cohesion with Digital Platforms to Realise a Good Social Society - Rasjid, A Ramli; Jannah, Intan Roudhatul; Al Khabir, Andi Shafwan; D, Shabila Salwa; Randi, Mohammad (Universitas Negeri Gorontalo, 2024)
Digital platforms are not only remodeling the way we interact but also offer new opportunities to build strong social cohesion. Analyzing various case studies and digital initiatives reveals how digital tools can expand social networks, deepen community participation, and instill constructive civic values. Through an exploration of innovative strategies and best practices, this article presents a practical guide to harnessing the power of digital platforms to create a more connected, engaged, and responsible society, thus making good citizens. The findings provide new perspectives on how technology can strengthen social fabric and advance quality citizenship in an increasingly connected world. This research aims to analyze the role of digital platforms in improving social cohesion by assessing the potential and challenges posed by using digital platforms such as social media, community apps, and online forums. Based on a survey of 50 respondents from campus and civilian populations, most people believe that digital platforms have great potential to strengthen relationships between individuals, expand social interactions, and increase solidarity within communities. However, the main challenges identified were social polarisation, the spread of misinformation, and the technology access gap that still exists in some communities. The findings emphasize the importance of thoughtful moderation policies, digital literacy education, and efforts to reduce social divides to maximize the positive potential of digital platforms. With the right approach, digital platforms can build a more inclusive and harmonious social society, which supports social cohesion among individuals and groups. This research provides important insights for policymakers and society on how to utilize digital technologies positively and constructively.